European Psychiatric Association guidance on assessment of cognitive impairment in schizophrenia. Issue 1 (5th September 2022) - Vita, Antonio; Gaebel, Wolfgang; Mucci, Armida; Sachs, Gabriele; Erfurth, Andreas; Barlati, Stefano; Zanca, Federico; Giordano, Giulia Maria; Birkedal Glenthøj, Louise; Nordentoft, Merete; Galderisi, Silvana
Abstract: Background: Impairment in a wide range of cognitive abilities has been consistently reported in individuals with schizophrenia. Both neurocognitive and social cognitive deficits are thought to underlie severe functional disabilities associated with schizophrenia. Despite the key role in schizophrenia outcome, cognition is still poorly assessed in both research and clinical settings. Methods: In this guidance paper, we provide a systematic review of the scientific literature and elaborate several recommendations for the assessment of cognitive functions in schizophrenia both in research settings and in real-world clinical practice. Results: Expert consensus and systematic reviews provided guidance for the optimal assessment of cognitive functions in schizophrenia. Based on the reviewed evidence, we recommend a comprehensive and systematic assessment of neurocognitive and social cognitive domains in schizophrenia, in all phases of the disorder, as well as in subjects at risk to develop psychosis. This European Psychiatric Association guidance recommends not only the use of observer reports but also self-reports and interview-based cognitive assessment tools. The guidance also provides a systematic review of the state of the art of assessment in the first episode of psychosis patients and in individuals at risk for psychosis. Conclusion: The comprehensive review of the evidence and the recommendations might contribute to advance the field, allowing a better cognitive assessment, and avoiding overlaps with other psychopathological dimensions. The dissemination of this guidance paper may promote the development of shared guidelines concerning the assessment of cognitive functions in schizophrenia, with the purpose to improve the quality of care and to obtain recovery.